A new deep-sea species of the genus Urocaridella (Crustacea: Decapoda: Caridea: Palaemonidea) from Yap Seamount in the Western Pacific - Wang, Yan-Rong; Chan, Tin-Yam; Sha, Zhong-Li (Zootaxa, 2015)
A new species of palaemonid shrimp, Urocaridella liui sp. nov., is discovered from deep waters on the Yap Seamount in the Western Pacific. The new species is unique in the genus by having a pronounced triangular protrusion on the third posterior part of the third pleonal tergite and the almost colorless body, as well as for its occurrence in waters deeper than 250 meters. Other distinct characteristics of this species are the arrangement of dorsal rostral teeth; shorter fingers of the first and second pereiopods and shorter dactyli of the posterior pereiopods; the ratio of the carpus/palm length of the first and second pereiopods; the slender, but not filiform third to fifth pereiopods; and rounded postero-ventrally margin of the fifth abdominal somite. A key to the species of Urocaridella is provided.